Did Darwin kill God? - Davis, Emily; Cunningham, Conor ([Australia : BBC Active, 2009)
Can Darwin and religion exist side by side? In this thought-provoking programme, Anglican Christian, philosopher and theologian Conor Cunningham explains why these two beliefs are not in conflict
Executive producer, Jean Claude Bragard ; camera, Doug Hartington, Mike Jackson ; film editor, Andrew Rushtan
DVD format
Keywords: Evolution -- Religious aspects; Creationism; Evolution (Biology) -- Religious aspects; Religion and science